Holointerferometric Method for Stress Measurement in Structures - Kiczko, A.; Ochelski, S. (Engineering Transactions, 1992)
Theoretical foundations of holografic-interferometric method to measure stresses in the civil engineering and mechanical structures are presented. A portable, mountable holographic camera is described. Stress measurement technique and processing of results are described.